Veterinary Contributions to Public Health Extend Beyond the Clinic with the U.S. Army Public Health Command - Hull, Dawn (My University, 2015)
This is a report of my field experience with the U.S. Army Public Health Command (USAPHC) Region North in Fort Belvoir, VA from November 2012 to June 2013 under the guidance and supervision of Major Robert Paul, DVM, MPH, DACVPM. My public health experiences continued past the scheduled timeframe with my reassignment to the USAPHC Region South District Fort Hood, TX from September 2013 to present. During this time, I was fortunate to have the consultation and mentorship of Major Angel Schmillen, DVM, MPH, DACVPM. This report will focus on the scheduled field experience, then touch on a few interesting scenarios which developed while assigned to PHC District Fort Hood. During my field experience, I was assigned an intern in the First Year Graduate Veterinary Education (FYGVE) program which included rotations through public health, veterinary clinical operations, and leadership. The public health and veterinary clinical rotations lasted at least three weeks each and allowed for successful completion of the planned learning objectives. The products developed from the field experience were multiple and included zoonotic disease client communication tri-folds, a joint agency approach to vector-borne disease surveillance, full credentialing as a commercial food facility auditor, and review of a biological risk mitigation application in a veterinary clinic. After the completion of the scheduled field experience, many unique scenarios developed which are worth mentioning under this field experience topic. The purpose of this report is to describe my field experience with USAPHC and describe how the Masters in Public Health core curriculum provided the knowledge base to detect areas for improvement and develop products to effectively promote preventive medicine and public health.
Keywords: US Army; Public Health Command